Assisting learning using computers through the application of animated pedagogical agents (APA) or intelligent agents - Junaidi, Juhazren (Persatuan Teknologi Pendidikan Malaysia, 2007)
This paper is a concept paper that will mainly discuss the on idea of applying Animated Pedagogical Agents (APA) or also known as Intelligent Agents into learning process. The paper intends to emphasise on the definition, the development overview of APA, its application in learning and the question of does it improve learning. The main field of discussion is Computer Based Learning, because APAs are implemented in learning using computers. It is hoped that this paper is a kickstart that will give a useful input to those interested in Artificial Intelligence in education.